Molecular mechanisms of pain in acute pancreatitis: recent basic research advances and therapeutic implications - Wu, Yongzi; Han, Chenxia; Luo, Rong; Cai, Wenhao; Xia, Qing; Jiang, Ruotian; Ferdek, Pawel E.; Liu, Tingting; Huang, Wei (Frontiers in Molecular Neuroscience, 2023)
Although severe abdominal pain is the main symptom of acute pancreatitis, its mechanisms are poorly understood. An emerging body of literature evidence indicates that neurogenic inflammation might play a major role in modulating the perception of pain from the pancreas. Neurogenic inflammation is the result of a crosstalk between injured pancreatic tissue and activated neurons, which leads to an auto-amplification loop between inflammation and pain during the progression of acute pancreatitis. In this review, we summarize recent findings on the role of neuropeptides, ion channels, and the endocannabinoid system in acute pancreatitis-related pain. We also highlight potential therapeutic strategies that could be applied for managing severe pain in this disease.